Kerangka Teoretis Integrasi Berpikir Komputasional dalam Pembelajaran Fisika Kuantum - Asep Irvan Irvani; Parlindungan Sinaga; Endi Suhendi; Lilik Hasanah; Rahmadhani Mulvia; Siti Nurdianti Muhajir (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the theoretical framework of Computational Thinking (CT) integration in quantum physics education, specifically to improve concept understanding, critical thinking dispositions & abilities, and creative problem-solving skills of prospective physics teachers. CT is viewed as a systematic cognitive approach capable of bridging the gap in students' understanding of abstract and mathematical concepts in quantum physics. This study employs a qualitative method using systematic literature review and conceptual analysis of theories, models, and relevant previous research findings, both in the field of physics education and science education in general. The results of the study indicate that CT principles have the potential to improve the quality of students' thinking processes in understanding and solving quantum physics problems logically, reflectively, and creatively. The theoretical framework developed offers the integration of CT into learning design through a problem-based approach and multiple representations, both unplugged and computer-assisted. The conclusion of this study is that CT is not only relevant but also strategic as a foundation for the development of innovative pedagogy in modern physics education. The implications of this study open opportunities for curriculum designers, lecturers, and researchers to adopt and develop CT-based learning strategies in complex courses such as quantum physics, as well as encourage further empirical research to test the effectiveness of the proposed model.